Identifying Surgical and Trauma Patients in New Zealand for Opioid-Related Pharmacoepidemiological Research: A Descriptive Study - Jiayi Gong; Amy Hai Yan Chan; Kebede Beyene; Alan Forbes Merry; Andrew Tomlin; Peter Jones (MDPI AG, 2022)
Unique aspects of New Zealand's (NZ) health system allow for a novel pharmacoepidemiologic approach to conducting population-based clinical research. A defined cohort of surgical and trauma patients would facilitate future studies into opioid utilisation, outcomes, and other questions related to surgery and trauma. We aimed to describe all patients admitted to a NZ hospital with trauma or to undergo surgery between 1 January 2007 to 31 December 2019. This was a retrospective population-based study involving all hospital centres in NZ. We excluded patients with hospitalisation episodes for surgery or trauma one year before the event. We identified 1.78 million surgical only patients, 633,386 trauma only, and 250,800 trauma with surgery patients. Trauma only patients had the highest prevalence of death within one year of event (17.8%), history of opioid dispensing (18.3%), mental health disorders (17.0%) and chronic pain (2.3%). Moreover, trauma patients also had the highest prevalence of those with higher comorbidity burden. We plan to use this dataset for future research into the prevalence and outcomes of persistent opioid use, and to make our dataset available to other researchers upon request. Our findings of significant differences between cohorts suggest studies should treat surgical and trauma patients separately.